Nanoformulated antimicrobial agents for central nervous system infections - Zhang, S.; Chen, Y.; Liang, J.; Wang, Shaobin; Liu, Lihong; Liu, Shaomin (American Scientific Publishers, 2017)
© 2017 American Scientific Publishers All rights reserved. Meningitis and encephalitis caused by bacteria and fungi are among the top 10 lethal types of infectious diseases. The treatment of brain infection is principally limited by the blood-brain barrier (BBB), which restricts the entry of antimicrobial agents to the desired central nervous system (CNS). To address this issue, many different nanoparticles conjugated with targeting ligands have been employed to increase CNS penetration of several antifungal drugs like amphotericin B and itraconazole. However, a wide spectrum of microorganisms have provoked the diseases, and some have developed multidrug resistance to nearly all commercially available antibiotics. Therefore, there is an urgent need to design unconventional nanostructures that possess both novel biocidal modes and brain targeting property. This review focuses on classical nanocarriers enabling brain delivery of loaded antibiotics as well as highlights recent progress in the fabrication of transactivator of transcription (TAT) peptide-containing nanoparticles to circumvent BBB and kill the pathogenic microbes in brain tissue. The later strategy, albeit imperfect, may allow nanoantibiotics to target, diagnose and treat brain infection simultaneously in an unprecedented manner.